EXPLORATION OF THE RELATIONSHIP BETWEEN INNOVATIVE BEHAVIOR AND SAFETY PERFORMANCE OF THE SEMARANG BASARNAS SAR TEAM - Kurniawan, Yudhi; Sukardi, Sukardi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
Safety performance in search and rescue institutions such as BASARNAS is very important but has not been widely researched in the Indonesian context. This study analyzes the relationship between safety leadership, safety training, innovative behavior, and safety performance at the BASARNAS Semarang Office. Using a quantitative approach, data was collected from 80 employees through an online questionnaire and analyzed with Structural Equation Modeling (SEM-PLS). The results show a significant beneficial influence of safety leadership and training on safety performance and innovative behavior. The main finding is the role of innovative behavior mediation in the relationship between safety leadership and safety performance. The study broadens the understanding of safety dynamics in the context of Indonesian public safety institutions, highlighting the importance of integrating innovation in safety management practices. Implications include leadership development that drives innovation and safety training design that stimulates creativity to improve overall safety performance.